Finite Element Analysis of Pipeline Upheaval Buckling with different Initial Imperfections - Mazuki, Muhammad Nashriq; Ismail, Al Emran (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Upheaval buckling is among the most common issues endangering the safe functioning of subsea pipelines, and it is caused by temperature and inner pressure increases. The finite element approach was used to investigate the upheaval buckling behaviors of five groups of pipeline segments with varying initial imperfection shapes in this research. ANSYS is utilized to create and analyze five imperfection models to forecast the critical buckling temperature, Mises stress distribution along the pipeline and the position of post-Upheaval Buckling. The aforementioned models are subjected to two analytical approaches that combine static and dynamic processes. Linear analysis is applied to carry out the assessment to the pipeline. The findings are in good agreement with previous test data. The obtained result shows that the post-buckling position is at the midpoint of pipeline segment which satisfies with recent investigation. Next, Mises stress distribution have been studied for the five groups of pipeline imperfection and comparison between them have been made successfully. The critical temperature for triggering buckling has been achieved by using the buckling load multiplier generated through ANSYS Eigenvalue Buckling. Finally, a comparison is made between the outcomes of this study and earlier studies, revealing the approaches towards the Upheaval Buckling assessment.